Optimal relay coordination for power system connected to distribution generators using particle swarm optimization - Oraibi, Al Iedani Saleh Khairullah (2022)
The electrical system consists of a group of parts that together form an integrated system that can be relied upon in providing electrical energy to the consumer. Due to the expansion of the electrical network, the inability to install huge generating stations in different areas, and electrical losses due to increased load consumption, the Distributive generators appeared. Despite the benefits of distributed generators in terms of increasing the reliability of the electrical system and saving energy in peak times and many others, connecting distribution generators leads to a clear defect in the coordination of the operating between the protection devices in the system due to the bidirectional current flow which affects the reduction or increases the operating time for each relay and the lack of continuity of sequential coordination in the work between the relays. This research aims to study the impact of connecting distribution generators on the protection devices in the system and how to reduce and treat this effect in different ways and compare them to determine the best and fastest methods. Two methods will be used to coordinate the relays in the system: the conventional method and the PSO algorithm method. There are two scenarios for each method: connecting the distributed generators and not connecting the distributed generators. The TMS values and operating time for all relays will be calculated, and a comparison between the two methods will be performed to determine the optimal possible operating time, and this will be done using MATLAB to run the algorithm and ETAP software to verify the results obtained in the two methods. it was found that the conventional method is usually easy in procedures, but complex in implementation, as it requires accuracy in transmitting information and dealing with many parameters, and any error at any stage will negatively affect the values obtained in the following stages, and we also noticed that the operating period of the relays last for a long time, which causes a danger to the system, while in PSO method the total operating time of the relays was reduced to about 19.38 seconds when the distribution generators were not connected, while the time difference between the two methods was about 34.67 seconds when the distribution generators were connected, with the coordination time interval remaining around 0.4 seconds. This technology has achieved exceptional success in coordinating relays for diverse topologies and kinds of electrical networks.